Revised checklist of the fishes of the Red Sea, including distribution in the Gulf of Suez and Gulf of Aqaba, with notes on endemism and Lessepsian migration - Golani, Daniel; Fricke, Ronald (Zootaxa, 2026)
The present checklist provides, for each species of the Red Sea, records from the Gulf of Suez, Gulf of Aqaba, and the Red Sea main basin together with its general distribution, English vernacular name and IUCN Red List status. This updated checklist enumerates 1,250 species, representing 165 families. Of these, 813 species are recorded from the Gulf of Aqaba and 350 from the Gulf of Suez. The list includes 65 species newly described to science since the last checklist of 2018. The most speciose families of Osteichthyes are Gobiidae (154 species), Labridae (85), Apogonidae (60), Blenniidae (41), Muraenidae (40), Carangidae (39), Pomacentridae (35), Lutjanidae (34), Syngnathidae (33), Epinephelidae (27), and Scorpaenidae (25). Among the Chondrichthyes, the most speciose families are Carcharhinidae (17 species) and Dasyatidae (11). The total number of endemic species in the Red Sea is 177 species, of which, 36 species are endemic to the Gulf of Aqaba and 12 to the Gulf of Suez.